Higher school education versus the use of information about professions - Elżbieta Sałata (Edukacja Ustawiczna Dorosłych)
The paper is an attempt to answer the question concerning using the information about professions for the educational offer in an academic institution. The first part constitutes the consideration over contemporary changes in higher education. There are several social determinants, among them: the development of information and communication technologies, the development of mass media, changes of the structure of qualification and professional mobility. Both civilisation changes and the development of science and technique influence the appearance of new professions and new work places. The information about professions being developed as a career counselling tool can be helpful in choosing or confirming the choice of the field of study or speciality. The information may also facilitate the development of a gradu-ate profile, selection of the content of education (syllabuses, modules) as well as identification and assessment of learning outcomes.